Surface Tension of FeS-Cu2S-Ni3S2 Matte Systems - Liu, Yanhui; Lv, Xuewei; Bai, Chenguang (Asian Journal of Chemistry, 2015)
A thermodynamic model for determining the surface tension of ionic system by considering the surface tension and molar volume of the pure sulfide components and their ionic radii was extended to the molten FeS-Cu2S-Ni3S2 matte system. The temperature dependence of the surface tensions for pure FeS, Cu2S and Ni3S2 have been determined and the calculated surface tensions based on the present model are in good agreement with the experimental values. The maximum error and the average error are 10.11 and 5.02 %, respectively.